2019
DOI: 10.18063/ijb.v5i2.238
|View full text |Cite
|
Sign up to set email alerts
|

A methodology to develop a vascular geometry for in vitro cell culture using additive manufacturing

Abstract: Today, additive manufacturing (AM) is implemented in medical industry and profoundly revolutionizes this area. This approach consists of producing parts by additions of layers of successive materials and offers advantages in terms of rapidity, complexity of parts, competitive costs that can be exploited and can lead to a significant advancement in biological research. Everything becomes technically feasible and gives way to a “techno-centered” approach. Many parameters must be controlled in this field, so it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Cellular viability and function will be compromised, and necrosis may further occur without a capillary network within a few hundred microns of cells[ 2 , 3 ]. Thus, many approaches such as microreplication, photolithography, and sacrificial molding have been proposed to organize the endothelial cells in the spatially predefined organization, with an attempt to build microvessels within the cell-laden constructs[ 4 - 8 ]. It has been demonstrated that the endothelial cells in the spatially predefined organization can significantly improve the speed and extent of the vascularization after implantation, compared to that in a random distribution[ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular viability and function will be compromised, and necrosis may further occur without a capillary network within a few hundred microns of cells[ 2 , 3 ]. Thus, many approaches such as microreplication, photolithography, and sacrificial molding have been proposed to organize the endothelial cells in the spatially predefined organization, with an attempt to build microvessels within the cell-laden constructs[ 4 - 8 ]. It has been demonstrated that the endothelial cells in the spatially predefined organization can significantly improve the speed and extent of the vascularization after implantation, compared to that in a random distribution[ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this July issue, 10 articles are covered. The topics range from the development of new bioinks[ 1 - 5 ] to new bioprinters such as microfluidics-based printers[ 6 , 7 ] and high precision inkjet printer[ 8 ], as well as in vitro 3D tissue models for tissue engineering[ 9 , 10 ].…”
mentioning
confidence: 99%